Resolution of chronic pelvic pain and abnormal uterine bleeding after Essure® surgical removal and laparoscopic sterilization: A case report - Gentile, Marco; Costanza, Antonio; Zinna, Mariaconcetta (Indian Journal of Case Reports, 2020)
Hysteroscopic sterilization with Essure® microinsert is a method of female permanent contraception. Complications of the procedure are malpositioning, unintended pregnancy, abnormal uterine bleeding, and chronic pelvic pain. We report the case of a 44-year-old patient presented to our hospital for chronic pelvic pain and abnormal uterine bleeding. She had 5 years before a hysteroscopic placement of an Essure® device. At hysteroscopy, both devices were removed and a laparoscopic bilateral salpingectomy was performed. The patient reported resolution of chronic pelvic pain and of abnormal uterine bleeding following surgical procedures. Pelvic pain is the main symptom described after Essure® insertion with an incidence of 4.2% regarding persistent pain. The patients should be informed about the risks and benefits of hysteroscopic and laparoscopic sterilization procedures.